DI-003 Off-label and unlicensed drug use in paediatric outpatients with nephrotic syndrome: an indonesian context. (25th February 2017) - Ramadaniati, H; Khairani, S; Permatasari, D; Tambunan, T
Abstract : Background: It is interesting to note that limited studies have been done on the off-label drug use in the area of paediatric nephrology. Furthermore, information on the use of off-label drugs, especially in paediatric patients with nephrotic syndrome, is still lacking in Indonesia. Nephrotic syndrome is responsible for one of major chronic diseases in children and subsequently patients should take their medicines long term. Purpose: To estimate the prevalence of off-label and unlicensed prescribing in paediatric outpatients with nephrotic syndrome in a major teaching hospital in Indonesia. Material and methods: A retrospective study was conducted in hospital using medical records from paediatric outpatients with nephrotic syndrome during the period January to December 2015. Patient and prescribing data were collected, and drugs were classified as on-label or off-label/unlicensed based on Indonesia National Drug Information (IONI). Thereafter, off-label drugs were categorised with a hierarchical system of age, indication, route of administration and dosage. Results: There were 1864 drugs with 70 different types of drugs prescribed to 89 patients. The data revealed that 1390 (74.5%) of the drugs prescribed were off-label/unlicensed. The majority use of off-label drugs was mainly due to age (n=1200; 88.9%) while the remaining reasons were due to dosage (n=134; 9.9%) and indication (n=16: 1.2%). With regards to therapeutic category, non-diuretic antihypertensive agents (n=689; 51%) and immunosuppressants (n=455; 33.7%) were the top two most frequent drug categories used in an off-label manner. The most commonly used off-label drugs were prednisone (n=286), lisinopril (n=171) and losartan (n=169). Further, it was found that prednisone also accounted for the most frequent unlicensed drug. Off-label prescribing was common in paediatric outpatients with nephrotic syndrome where every patient received at least one off-label drug. It appears that off-label prescribing was not affected by patient age or gender. Conclusion: Despite the high prevalent of off-label prescriptions in paediatric outpatients with nephrotic syndrome, this use conformed to evidence based prescribing. Measures should be conducted to support clinical trials in paediatrics and subsequently revise IONI as the standard drug information in Indonesia. References and/or acknowledgements: We would like to acknowledge the Faculty of Pharmacy Pancasila University for granting research funding to support this study. No conflict of interest